Elastic band exercise induces greater neuromuscular fatigue than phasic isometric contractions; Journal of Electromyography and kinesiology; Vol. 47 - Grospretre S. Sidney; Gimenez P. Philippe; Mourot L. Laurent; Coratella G. Giuseppe (2019, 2019)
Title screen